Research review of epidemic history, causes and problems during epidemics: وباؤں کی تاریخ ، اسباب اور وباؤں کے دوران درپیش مسائل کا تحقیقی جائزہ - Iqbal, Dr. Farzan; Kulsoom, Aabroo (Al Khadim Research Journal of Islamic Culture and Civilization, 2021)
Trouble is the result of man’s evil deeds. It is known from Qur’an and Sunnahthat the troubles that befell human beings are man’s own deeds When these negative effects exceed the limit, then the deadly effects begin to appear and there is no specific way to prevent them. These are the motivesDue to which we are suffering from an epidemic like Corona virus.Islamic teachings contain guidance for every age and every issuebecause the guidance of Allah is sufficient for whole living world This guidance is obtained by each person according to divine mercy from his knowledge and observation. The solution to the problems encountered during this dangerous virus in modern times is also present in the Qur’an and Sunnahwhich guides us and in order to seek guidance in this regard, Muslims must seek the knowledge of scholars who know the Qur’an and Sunnah